PENGARUH BENTUK DINDING GESER TERHADAP DEFORMASI GEDUNG PADA GEMPA ZONE 5 - Arifien Nursandah (Universitas Muhammadiyah Surabaya, 2016)
ABSTRACTIn the earthquake zone 5 ( five ) need careful consideration so that the structural design of the building should be earthquake resistant . One type of earthquake-resistant structure is a double system with bearer Special Moment Frame System ( SRPMK ) and ShearWall ( SW ) . SRPMK is a system of order that in addition to meeting the provisions for bearer ordinary moment frame also meet the provisions of 23.2 to 23.5 by the rules